Development of Athletic Instructional Learning Media Based on Android Studio and Adobe Animete Applications in 2020 - Rizky Hasan Azhari Ritonga; Imran Akhmad; M. Irfan (Universitas Negeri Medan, 2020)
This research is motivated by the lack of interesting learning media innovations that exist for learning PJOK, especially athletics and the difficulty of some students in understanding the basic athletic movements taught in schools because of the lack of student interest in learning PJOK, especially athletics when in class or learning theory. This study aims to develop an Athletic Smart Apps application with athletic materials, especially the shooting and javelin throwing branches based on Android Studio and Adobe Animate for VII grade junior high school students. This research is a about development research or Research and Development which uses the Borg and Gall development model. The research and development stages consist of: (1) Research on existing products, (2) literature studies and field studies, (3) planning to make product designs. (4) Internal testing of designs, (5) Revising designs, (6) Making products, (7) Conducting limited trials, (8) Conducting product revisions 1, (9) Conducting main field trials, (10) Conducting product revision 2. Validation is carried out by material experts and media experts. The media developed was tested on 35 students of class VII-A SMP N3 Huraba Mandailing Natal. The results of this research were obtained: 1. The creation of an application product for the development of an athletic instructional instructional media application based on Android Studio and Adobe Animate for grade VII students of SMP N3; 2. Feasibility has been well tested in terms of material, media and usability factors with the category